2012
DOI: 10.1093/bja/aes155
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative sore throat: a multifactorial problem

Abstract: may be a contributing factor to the result in this study? Similarly, the type of analgesia used for laparoscopic surgery could also be open to review, with the use of epidurals, again extrapolated from open surgery, being shown to prolong the hospital length of stay in this group. 3 Could this also have a bearing on the results, although in this case, thoracic epidural analgesia (TEA) was used in both arms of this section of the trial? As with many good studies, this raises more questions than it directly answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…This study confirmed that postoperative sore throat is a common problem in postoperative patients as shown in the literature [17, 18]. …”
Section: Discussionsupporting
confidence: 90%
“…This study confirmed that postoperative sore throat is a common problem in postoperative patients as shown in the literature [17, 18]. …”
Section: Discussionsupporting
confidence: 90%
“…Baseline clinical data were derived from medical and follow-up records and included age, sex, body mass index (BMI), thyromental distance (TMD; with the neck fully extended, the distance from the thyroid notch to the chin projection was measured with a tape measure), position during surgery (including supine or non-supine position, with the latter including prone and lateral positions), surgical site (head and neck surgery (HNS) or non-head and neck surgery (NHNS), with the patients divided into the HNS group and the NHNS group), duration of anaesthesia (<4 hours or ≥4 hours), airway management (laryngeal mask or ETT), use of lidocaine cream (lidocaine cream or paraffin oil was used for tube lubrication), use of dexamethasone (prophylactic use of 10 mg within 10 min after intubation), history of smoking, history of chronic pharyngitis (patients with pre-existing sore throat were excluded, which means patients who currently have a sore throat were excluded from the entire study; ‘history of chronic pharyngitis’ means frequent pharyngitis but not currently active), postoperative analgesia (various medications including analgesics and antiemetics) and placement of a gastric drainage tube. The clinical variables associated with POST were assessed a priori based on clinical importance, scientific knowledge and predictors identified in previously published articles 6–8…”
Section: Methodsmentioning
confidence: 99%
“…Multiple factors are involved in the pathogenesis of POST following endotracheal intubation, which is mainly caused by the inflammatory response to intubation and the presence of the endotracheal tube (ETT) [31,32]. Furthermore, the localized inflammatory response could be aggravated by ETT motion induced by the neck hyperextension and manipulation during surgery [33,34].…”
Section: F I G U R E 2 Quality Of the Included Studies A: Risk Of Bmentioning
confidence: 99%